An electroactive multifunctional hydrogel and its preparation method and use
By developing an electroactive multifunctional hydrogel that combines conductive polymers and methacrylate hyaluronic acid, and introducing nanoparticles, the bioelectric signal interruption problem in the infarction area caused by ischemic stroke is solved, and the resistance to resistance Oxidation, anti-inflammatory and neurorepair effects.
Patent Information
- Application Number
- CN202411470456.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
Insufficient blood supply in the brain tissue caused by ischemic stroke leads to severe nerve damage, and existing treatment methods are difficult to effectively restore bioelectric signal transmission in the infarction area, and secondary complications exist.
Develop an electroactive multifunctional hydrogel that forms a dual crosslinked electroactive hydrogel through the combination of conductive polymers and methacrylate hyaluronic acid, and introduces drug-loaded nanoparticles to achieve continuous conductivity and drug release.
The hydrogel can provide continuous conductivity in the infarction zone, exert antioxidant, anti-inflammatory and anti-apoptotic effects, and supports nerve repair by continuously releasing the drug acetam, effectively solving the problem of bioelectric signal interruption in the infarction zone. .
Smart Images

Figure CN118986864B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and in particular relates to an electroactive multifunctional hydrogel and a preparation method and application thereof. Background Art
[0002] Ischemic stroke (IS) is a major killer that endangers life and health. Its morbidity and mortality rates continue to rise as the population continues to grow. Worryingly, the age of stroke onset is gradually getting younger. IS is an acute cerebrovascular disease characterized by cerebral vascular obstruction, which leads to insufficient blood supply to the brain tissue, which in turn causes brain tissue damage. In severe cases, it can cause high disability and mortality rates.
[0003] Thrombolytic therapy uses drugs to dissolve blood clots, while mechanical thrombectomy directly removes clots that block blood vessels through catheters and other tools. However, the current reperfusion therapy rates in most countries around the world are generally low. In addition, these treatments can cause secondary complications such as cognitive and psychiatric disorders, hemiplegia, swallowing disorders, and speech dysfunction. For stroke survivors, there is still a significant clinical burden and a lack of drug treatments to promote recovery.
[0004] When a cerebral artery is blocked by an embolus or thrombus, blood flow to the affected brain region is significantly reduced or stopped. The complex mechanisms of brain damage after ischemic stroke (IS) include neuroinflammatory response, oxidative stress injury, mitochondrial dysfunction, and excitotoxicity. IS often leads to severe neurological damage, and bioelectric signals are essential for the maturation and development of the nervous system. Therefore, restoring bioelectric signal transmission in the infarct area immediately after stroke is a major challenge in post-stroke treatment. In addition to bioelectric signals, the pathological progression of ischemic stroke (IS) is a dynamic process. In the early stage of ischemia, the disease progresses rapidly, so antioxidant therapy becomes the main focus of treatment. However, in the later stage of neurological function recovery, the focus of treatment shifts to neurorepair. Therefore, in order to provide a long-lasting and effective treatment plan, it is urgent to develop a multifunctional therapeutic system that can play different roles at different stages of the disease, so as to play antioxidant, anti-apoptotic and anti-inflammatory roles in the early stage of IS, and support neurorepair function in the late stage of IS. Summary of the invention
[0005] The purpose of the present invention is to provide an electroactive multifunctional hydrogel and a preparation method and use thereof.
[0006] The present invention provides an electroactive multifunctional hydrogel, the raw materials of which include a conductive polymer and methacrylated hyaluronic acid, wherein the conductive polymer is a product obtained by reacting gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid as raw materials under the action of an initiator.
[0007] Further, the mass ratio of the conductive polymer to the methacrylated hyaluronic acid is 0.5-3:8;
[0008] The ratio of gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid is 15-25 g: 600-650 μL: 1.5-2.5 g: 4.0-6.0 g, the initiator is a peroxide initiator, and the mass ratio of gelatin to initiator is 3-5:1;
[0009] Furthermore, the mass ratio of the conductive polymer to the methacrylated hyaluronic acid is 2:8;
[0010] The ratio of the gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid is 20g:630μL:1.8g:5.0g, the peroxide initiator is ammonium persulfate, and the mass ratio of the gelatin to the initiator is 4:1.
[0011] Furthermore, the reaction is carried out in an acidic solution, the reaction temperature is 50-70° C., and the reaction time is 20-28 hours.
[0012] Furthermore, the acidic solution is a 0.2 M hydrochloric acid solution, the reaction temperature is 60° C., and the reaction time is 24 hours.
[0013] Furthermore, the methacrylated hyaluronic acid is a product prepared using hyaluronate and methacrylic anhydride as raw materials, and the hyaluronate is preferably sodium hyaluronate.
[0014] Furthermore, the raw materials of the electroactive multifunctional hydrogel also include nanoparticles, and the preparation method of the nanoparticles includes the following steps: a non-ionic surfactant and an antioxidant compound react to obtain an intermediate product, dissolving the intermediate product in an organic solvent, concentrating, dispersing it in an aqueous solution, and drying to obtain the nanoparticles.
[0015] Furthermore, the organic solvent is an organic solvent containing a brain function improving drug.
[0016] Further, the nonionic surfactant is Pluronic F127, the antioxidant compound is lipoic acid, and the brain function improving drug is aniracetam;
[0017] The mass ratio of the nonionic surfactant to the antioxidant compound is (13-17):1, and the mass ratio of the intermediate product to the brain function improving drug is (1.5-2.0):1.
[0018] Furthermore, the mass ratio of the nonionic surfactant to the antioxidant compound is 15:1, the mass ratio of the intermediate product to the brain function improving drug is 1.7:1, and the organic solvent is ethyl acetate.
[0019] Furthermore, the nonionic surfactant and the antioxidant compound react under the action of a catalyst, and the catalyst is preferably 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine.
[0020] The present invention also provides a method for preparing the above-mentioned electroactive multifunctional hydrogel, the method comprising the following steps: reacting a conductive polymer and methacrylated hyaluronic acid in an aqueous solution under the action of a peroxide and an amine compound to obtain;
[0021] Alternatively, the method comprises the following steps: reacting the conductive polymer and methacrylated hyaluronic acid in an aqueous solution under the action of peroxide and diamine compounds, drying the obtained product, then immersing it in an aqueous solution of nanoparticles, and taking it out to obtain the product.
[0022] Furthermore, the peroxide is ammonium persulfate, and the diamine compound is N,N,N',N'-tetramethylethylenediamine; in the aqueous solution of the nanoparticles, the concentration of the nanoparticles is 6-10 mg / mL.
[0023] Furthermore, in the aqueous solution of the nanoparticles, the concentration of the nanoparticles is 6 mg / mL.
[0024] Furthermore, the aqueous solution is water or a buffer solution.
[0025] Furthermore, the drying is freeze-drying.
[0026] The present invention also provides use of the electroactive multifunctional hydrogel in preparing a medicine for improving brain function.
[0027] Furthermore, the drug is a drug for preventing and / or treating ischemic stroke.
[0028] Furthermore, the drug is a drug that has the effect of restoring nerve function and motor function.
[0029] Furthermore, the drug is an in-situ gel for injection.
[0030] The present invention has achieved the following beneficial effects:
[0031] The present invention first synthesizes a conductive material, namely gelatin (GT)-polyaniline-3-aminophenylbenzenesulfonic acid (BSA)-3-aminophenylboronic acid (PBA) complex (GM for short). In GM, polyaniline can be transformed from a non-conductive state to a highly conductive state by doping with acid. The present invention successfully introduces BSA and PBA into the side chain of polyaniline, thereby synthesizing polyaniline with a conjugated main chain and anionic side chains. This design overcomes the problem of poor dispersibility of traditional polyaniline in water.
[0032] In the present invention, GM and methacrylated hyaluronic acid (HAMA) are subjected to free radical polymerization, and a double-crosslinked electroactive hydrogel is obtained through non-covalent crosslinking of GM dynamic borate bonds and negatively charged HAMA; nanoparticles (PSA NPs) loaded with the drug aniracetam are further introduced into the double-crosslinked electroactive hydrogel to prepare an electroactive multifunctional hydrogel similar to ECM. The electroactive multifunctional hydrogel of the present invention can provide continuous conductivity, sequentially exert antioxidant effects, inhibit inflammation and apoptosis, continuously release the drug aniracetam, and be used for later nerve repair, effectively solving the challenge of interruption of bioelectric signals in the infarct area, and proposing a promising new method for sequential treatment of ischemic stroke.
[0033] The experimental results show that the multifunctional hydrogel prepared by the present invention realizes the stable conductivity of the hydrogel and the rapid response and regulation to the inflammatory microenvironment. The hydrogel is prepared by triple crosslinking through free radical polymerization of methacrylated hyaluronic acid (HAMA), formation of dynamic borate bonds and non-covalent crosslinking. This not only gives the hydrogel good injectability, but also ensures that the hydrogel can maintain good conductivity to establish electrical signals between damaged tissues in a timely and continuous manner. At the same time, nanoparticles can be quickly released in the infarct area to reshape the microenvironment. In addition, the modulus of the multifunctional hydrogel prepared by the present invention matches the modulus of the mouse cerebral cortex, and can be well injected and filled in the cerebral infarction area, effectively solving the challenge of interruption of bioelectric signals in the infarction area, and proposing a promising new method for sequential treatment of ischemic stroke.
[0034] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0035] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1: Structural characterization results and injectability test results of the samples. (A) FTIR spectra of GT, GM, HA and HAMA; (B) FTIR spectra of GM and HAMA 1 HNMR spectrum; (C) Demonstration of the injectability of HA / GM hydrogel.
[0037] Figure 2 :(A)Conductivity results of HA / GM hydrogel under different GM concentrations (n=9);(B)Biocompatibility results of HA / GM hydrogel (n=6). ns: p>0.05, ***p<0.001,****p<0.0001.
[0038] Figure 3 : Antioxidant activity of PSA NPs at different concentrations (n=3).
[0039] Figure 4 : (A) CV curve, (B) Bode plot and (C) Nyquist plot of HA / GM / PSA hydrogel; (D) Cumulative release efficiency of aniracetam in HA / GM / PSA hydrogel (n=3). ***p<0.001, ****p<0.0001.
[0040] Figure 5 : In vivo experimental results of hydrogel treatment of IS. (A) Falling time in the rotation test (week 1 and week 4); (B) total distance in the open field test and (C) movement speed test results. DETAILED DESCRIPTION
[0041] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0042] Hyaluronic acid (HA, molecular weight: 10 × 10 4 Da) was purchased from Guanglong Biotechnology (Qufu, China), gelatin (GT, 240 g bloom) was purchased from Adamas (China), and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC, >98%), N-hydroxysuccinimide (NHS, >97%), and lipoic acid (LA) were purchased from Aladdin Industries (Shanghai, China).
[0043] Mouse hippocampal neurons (HT22) and immortalized mouse microglia (BV2) were purchased from Shanghai Fuheng Biotechnology Co., Ltd.
[0044] Cell counting kit-8 (CCK8) and reactive oxygen species (ROS) detection kit were purchased from Beyotime (China), live / dead cell staining kit was purchased from APExBIO (USA), fetal bovine serum (FBS), Dulbecco’s modified Eagle’s medium (DMEM), and trypsin were purchased from Gibco (USA), all enzyme-linked immunosorbent assay (ELISA) kits were purchased from Boster (China), TUNEL kit was purchased from Novezan (Nanjing, China), and all materials were purchased from Sigma-Aldrich (USA) unless otherwise noted.
[0045] Example 1. Preparation of electroactive HA / GM hydrogel without nanoparticles
[0046] 1. GM synthesis:
[0047] 20 g of gelatin (GT) was dissolved in 200 mL of 0.2 M hydrochloric acid solution at 60 °C. After the gelatin was completely dissolved, 630 μL of aniline, 1.8 g of 3-aminophenylboronic acid and 5.0 g of 3-aminobenzenesulfonic acid were added and stirred at room temperature until dissolved. Then 5.02 g of ammonium persulfate (APS) was added and the reaction was continued with stirring for 24 hours. Finally, the obtained product was dialyzed for 3-5 days and then freeze-dried to obtain gelatin-polyaniline-3-aminobenzenesulfonic acid-3-aminophenylboronic acid polymer, referred to as GM.
[0048] 2. Synthesis of methacrylated hyaluronic acid (HAMA):
[0049] Dissolve 2g of sodium hyaluronate in 200ml of deionized water and stir overnight at 4°C. Then, slowly add 5ml of methacrylic anhydride and add 1 mol / L NaOH solution to keep the pH of the solution between 8.0 and 9.0. The mixed solution is magnetically stirred overnight at 4°C and then precipitated with ethanol. The precipitate is placed in a refrigerator at 4°C for 4 days for dialysis and then freeze-dried to obtain HAMA.
[0050] 3. Preparation of HA / GM hydrogel
[0051] 500 mg HAMA was dissolved in PBS and stirred continuously under magnetic stirring at room temperature for 4 hours to obtain HAMA solution. GM solutions of different concentrations (solvent: PBS) and the aforementioned HAMA solution were mixed at a volume ratio of 1:5, so that the final concentration of HAMA in the mixed solution was 8 wt%, and the final concentration of GM was 0 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt% or 3.0 wt%. Subsequently, 40 ul of 5% APS and 8 ul of N,N,N',N'-tetramethylethylenediamine (TEMED) were added and reacted for 1 min to prepare double-crosslinked electroactive hydrogels with different GM contents, namely HA / GM hydrogels.
[0052] Among them, the hydrogel obtained when the final concentration of GM is 0 wt% is also called HA hydrogel.
[0053] Example 2. Preparation of electroactive HA / GM / PS hydrogel without aniracetam
[0054] 1. GM synthesis:
[0055] Same as step 1 in Example 1.
[0056] 2. Synthesis of HAMA:
[0057] Same as step 2 of Example 1.
[0058] 3. Synthesis of PS NPs:
[0059] 9 g of Pluronic F127 (PF127), 0.6 g of lipoic acid, 1.2 g of EDC, and 0.36 g of 4-dimethylaminopyridine (DMAP) were weighed into a two-necked round-bottom flask. Under nitrogen protection, 55 mL of dichloromethane (DCM) was added to the round-bottom flask and reacted in the dark for 24 hours. Then, the solvent DCM was concentrated by distillation under reduced pressure. The concentrated product was added dropwise to ice ether and filtered by suction to obtain PF127-S.
[0060] Nanoparticles were prepared using the Bangham method. Specifically, 10 mg of PF127-S was completely dissolved in 8 mL of ethyl acetate, and then the ethyl acetate was concentrated by rotary evaporation. Finally, 5 mL of deionized water was added and freeze-dried after ultrasonication for 15 min to obtain PS NPs.
[0061] 4. Preparation of HA / GM / PS Hydrogel
[0062] 500 mg HAMA was dissolved in PBS and stirred continuously under magnetic stirring at room temperature for 4 hours to obtain HAMA solution. GM solution of different concentrations (solvent: PBS) and the above HAMA solution were mixed at a volume ratio of 1:5, so that the final concentration of HAMA in the mixed solution was 8wt%, and the final concentration of GM was 0 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt% or 3.0 wt%. Subsequently, 40 ul of 5% APS and 8 ul of N,N,N',N'-tetramethylethylenediamine (TEMED) were added and reacted for 1 min to prepare double cross-linked hydrogel. After freeze-drying the double cross-linked hydrogel, it was immersed in 6 mg / mL PS NP (solvent: PBS) for 48 hours, and the electroactive HA / GM / PS hydrogel with different GM contents was obtained.
[0063] Example 3. Preparation of electroactive HA / GM / PSA hydrogel
[0064] 1. GM synthesis:
[0065] Same as step 1 in Example 1.
[0066] 2. Synthesis of HAMA:
[0067] Same as step 2 of Example 1.
[0068] 3. Synthesis of PSA NPs:
[0069] 9 g of Pluronic F127 (PF127), 0.6 g of lipoic acid, 1.2 g of EDC, and 0.36 g of 4-dimethylaminopyridine (DMAP) were weighed into a two-necked round-bottom flask. Under nitrogen protection, 55 mL of dichloromethane (DCM) was added to the round-bottom flask and reacted in the dark for 24 hours. Then, the solvent DCM was concentrated by distillation under reduced pressure. The concentrated product was added dropwise to ice ether and filtered by suction to obtain PF127-S.
[0070] Nanoparticles were prepared using the Bangham method. Specifically, 10 mg of PF127-S and 6 mg of aniracetam were dissolved in 8 mL of ethyl acetate, and then the ethyl acetate was concentrated by rotary evaporation. Finally, 5 mL of deionized water was added, and the mixture was sonicated for 15 min and freeze-dried to obtain PSA NPs.
[0071] 4. Preparation of HA / GM / PSA hydrogel:
[0072] 500 mg HAMA was dissolved in PBS and stirred continuously under magnetic stirring at room temperature for 4 hours to obtain HAMA solution. GM solutions of different concentrations (solvent: PBS) and the above HAMA solution were mixed at a volume ratio of 1:5, so that the final concentration of HAMA in the mixed solution was 8wt%, and the final concentration of GM was 0 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt% or 3.0 wt%. Subsequently, 40 ul of 5% APS and 8 ul of N,N,N',N'-tetramethylethylenediamine (TEMED) were added and reacted for 1 min to prepare a double cross-linked hydrogel. After freeze-drying the double cross-linked hydrogel, it was immersed in 6 mg / mL PSA NPs (solvent: PBS) for 48 hours, and the electroactive hydrogels with different GM contents were obtained after being taken out, which were named HA / GM / PSA hydrogels.
[0073] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0074] All statistical analyses in the following experiments were performed using GraphPad Prism software (version 8.0). The results are expressed as mean ± standard deviation (SD). Statistical significance between groups was assessed using one-way ANOVA and is expressed as ns p>0.05, *p<0.05, **p<0.01, ***p<0.001 and ****p<0.0001.
[0075] Experimental Example 1. Conductivity and biocompatibility test of HA / GM hydrogel
[0076] 1. Experimental methods
[0077] (1) Structural characterization
[0078] Fourier Transform Infrared Spectroscopy (FTIR) Analysis:
[0079] FTIR spectra of the samples were collected using an FTIR spectrometer (Nicolet 67, Thermo Nicolet, USA). Each sample consisted of 1 mg of powdered material mixed with 100 mg of potassium bromide (KBr) powder. The spectra were recorded in the range of 500 to 4000 cm⁻¹, with 64 scans per sample and a resolution of 4 cm⁻¹.
[0080] Hydrogen nuclear magnetic resonance spectroscopy (1H NMR) characterization:
[0081] The samples were analyzed by NMR (Avance NEO-400 MHz, Bruker, Germany) in deuterated chloroform (CDCl 3) or deuterated water as solvent.
[0082] (2) Conductivity test of HA / GM hydrogel:
[0083] First, the conductivity of the hydrogel was visually evaluated by a light-emitting diode and a conductive pen. The electrical resistance of the conductive hydrogel was measured using a TruEbox 01RC, and the conductivity was then calculated using the following formula:
[0084] σ = L / (R×S) (1)
[0085] where L is the length between adjacent electrodes, R and S are the resistance and cross-sectional area of the hydrogel sample, respectively.
[0086] (3) Cytocompatibility assay:
[0087] Establishment of oxygen-glucose deprivation (OGD) model: High glucose DMEM complete medium with 10% fetal bovine serum and 1% penicillin / streptomycin was used for routine cell culture. To establish the OGD model, cells were kept at 37°C and 5% CO 2 , 94% N 2 and 1% O 2 The cells were then cultured in DMEM without D-glucose for 2 hours under the conditions of 1% to 5% saturation. The cells were then returned to standard culture conditions and the DMEM without D-glucose medium was replaced with complete medium for a further 24 hours.
[0088] To evaluate the safety of the hydrogels on HT22 and BV2 cells, CCK-8 assays were performed using different hydrogel extracts. HT22 and BV2 cells were seeded in 96-well plates at a density of 6 × 10³ cells per well and cultured for 24 h before treatment for OGD process (2 h), then the D-glucose-free DMEM medium was replaced with hydrogel extracts, and cell viability was measured using CCK-8 kit after 48 h of culture (n=6). Live / dead cell staining was performed according to the instructions (n=6). Control cells were cultured as usual.
[0089] The above experimental samples were hydrogel extracts, which were prepared as follows: 1 g of hydrogel was soaked in complete culture medium (5 mL, pH 6.5 and 200 μM H 2 O 2 ) for 72 hours to obtain a hydrogel extract. The hydrogel used was HA / GM hydrogel.
[0090] 2. Experimental results
[0091] The FTIR spectra of GT, GM, HA and HAMA are shown in Figure 1 As shown in A, GM and HAMA 1HNMR spectrum Figure 1 B. The present invention forms HA / GM conductive hydrogel through free radical polymerization of HAMA, dynamic borate bond crosslinking and electrostatic adsorption of HAMA and GM. First, GM was prepared by chemical oxidative free radical graft polymerization, and BSA and PBA were introduced to convert polyaniline from a non-conductive form to a highly conductive form. HAMA was synthesized by reacting methacrylic anhydride with hyaluronic acid. The free radical polymerization of HAMA and the borate bond formed between the ortho-dihydroxyl group in HAMA and the borate group in GM ensure the dynamic properties of the polymer network. In addition, the HA / GM hydrogel is also enhanced by the hydrogen bond between -COOH and -NH. The gelation time of the hydrogel is about 30s.
[0092] The injectability of HA / GM hydrogel was effectively improved by electrostatic interaction between positively charged GM and negatively charged HAMA, as well as dynamic cross-linking boronate bonds and non-covalent cross-linking (see Figure 1 C). In order to further explore the electrical properties of HA / GM hydrogels, this experiment used conductivity as an indicator to characterize the conductivity of GM hydrogels with different final concentrations. Figure 2 As shown in Figure 1, the conductivity of the hydrogels gradually increased with the increase of GM content. Compared with the HA hydrogel, the conductivity increased by 55.00%. However, when the final GM concentration was higher than 2.0%, there was no significant difference in the conductivity between the HA / GM hydrogels.
[0093] Next, the biocompatibility of HA / GM hydrogels was evaluated. The results showed that when the final concentration of GM exceeded 2.0%, the activity of HT22 cells decreased ( Figure 2 B). Therefore, HA / GM hydrogels with a final GM concentration of 2.0% were selected for subsequent experiments.
[0094] Finally, in this experiment, HA hydrogel and HA / GM hydrogel with a final GM concentration of 2.0% were connected to the circuit and tested with a light-emitting diode (LED) and a conductive pen. The results showed that the brightness of the LED light and the conductive pen in the HA / GM hydrogel group was significantly higher than that in the HA hydrogel group.
[0095] The results show that the HA / GM hydrogel prepared by the method of the present invention not only has good electrical conductivity between tissues, but also has excellent biocompatibility. Taking the above two properties into consideration, the HA / GM hydrogel has the best comprehensive performance when the final GM concentration is 2.0%.
[0096] Experimental Example 2. Characterization of the physicochemical properties of HA / GM / PSA hydrogel
[0097] 1. Experimental methods
[0098] Fourier Transform Infrared Spectroscopy (FTIR) Analysis:
[0099] FTIR spectra of the samples were collected using an FTIR spectrometer (Nicolet 67, Thermo Nicolet, USA). Each sample consisted of 1 mg of powdered material mixed with 100 mg of potassium bromide (KBr) powder. The spectra were recorded in the range of 500 to 4000 cm⁻¹, with 64 scans per sample and a resolution of 4 cm⁻¹.
[0100] H NMR spectroscopy ( 1 H NMR) Characterization:
[0101] The samples were analyzed by NMR (Avance NEO-400 MHz, Bruker, Germany) in deuterated chloroform (CDCl 3 ) or deuterated water as solvent 1 H NMR.
[0102] Determination of nanoparticle size, zeta potential, morphology, encapsulation efficiency (EE) and drug loading efficiency (DLE):
[0103] The dried nanoparticles were dispersed in distilled water and their particle size and zeta potential were characterized by Nano-ZS Zetasizer analyzer (Malvern Instruments, UK). Transmission electron microscopy (TEM) was used to obtain morphological images of the nanoparticles (H-600 microscope, Hitachi, Japan). In addition, UV spectrophotometry was used to verify the successful drug loading of PSA NPs.
[0104] Aniracetam was dissolved in ethyl acetate, and its maximum absorption wavelength was determined by UV spectrophotometer and a standard curve was drawn. PSA NPs were prepared using aniracetam (W0), and the encapsulation efficiency of PSA NPs was determined by high-speed refrigerated centrifugation (temperature: 4°C, speed: 15,000 rpm / min, centrifugation time: 20 min). The nanoparticle precipitate was freeze-dried and weighed (W1). It was redissolved in ethyl acetate and the drug mass in PSA NPs was determined (W2). The EE and DLE of PSA NPs were calculated using the following formula:
[0105] EE (%) = W 2 / W 0 ×100 (1)
[0106] DLE (%) = W 2 / W 1 ×100 (2)
[0107] Among them, W 0 is the total mass of aniracetam, W 1 is the total mass of the nanoparticles, W 2 is the mass of encapsulated aniracetam.
[0108] Morphology and swelling ratio (SR) of hydrogel:
[0109] The morphology of the hydrogels was analyzed using scanning electron microscopy (SEM) (GeminiSEM 360, Zeiss, Germany). Before observation, the freeze-dried hydrogels were metal-plated. In addition, energy dispersive spectroscopy (EDS) mapping was used to confirm the elemental composition.
[0110] The freeze-dried hydrogel (M 0 , n=3) were weighed and immersed in PBS (pH=7.4) and PBS (pH=6.5, containing H 2 O 2 ) and the temperature was maintained at 37°C. The swollen hydrogel samples were taken out at different time points, and the excess water on the sample surface was removed with filter paper and then weighed (M n ).
[0111] SR (%) = (M n − M 0 ) / M 0 × 100 (3)
[0112] Antioxidant properties of PSA NPs and hydrogels:
[0113] The antioxidant activity of PSA NPs and hydrogels was evaluated by measuring their scavenging effect on DPPH free radicals. 1 ml of DPPH solution (0.1 mmol / L) was added to PSA NPs solutions of different concentrations and different hydrogels, and then placed at room temperature for 24 hours. The absorbance was measured by UV spectrophotometer, and the DPPH scavenging rate was calculated.
[0114] Rheological study of hydrogels:
[0115] The rheological properties of the hydrogels were evaluated using an MCR302 modular compact rheometer (Anton Paar GmbH, Austria). Steady-state shear flow experiments were performed using a double concentric cylinder geometry with a gap of 4 mm. Frequency sweeps were performed at a fixed strain of 1% by sweeping the oscillation frequency from 1 to 100 rad s⁻¹. For the strain sweep, the oscillation frequency was fixed at 1 Hz and the strain range was from 1% to 100%.
[0116] Electrochemical properties of HA / GM / PSA hydrogels:
[0117] Cyclic voltammetry (CV) measurements and electrochemical impedance spectroscopy (EIS) measurements were performed at room temperature using an electrochemical workstation (CHI760E, China) with an electrode system. 1 mL of the hydrogel precursor solution was prepared into a strip with a width of 1 cm and a height of 2 cm. EIS measurements were performed in the frequency range of 1 MHz to 0.1 Hz.
[0118] In vitro drug release from hydrogels:
[0119] The hydrogels (N0, n=3) were weighed and immersed in PBS (pH=7.4) and PBS (pH=6.5, 200 μM H 2 O 2 ) and the temperature was maintained at 37°C. 1 mL of release medium was removed at different time intervals and replaced with an equal amount of fresh release medium. The released aniracetam was quantified by UV spectrophotometry.
[0120] 2. Experimental results
[0121] Considering the high ROS status and persistent inflammatory response in the infarcted brain where the conductive hydrogel works, nanoparticles with good antioxidant properties and neurorepair properties were prepared in this experiment. LA containing disulfide bonds was grafted onto PF127 through esterification reaction to prepare PF127-S polymer. The synthesized PF127-S polymer was characterized and 1 HNMR and FTIR were used to confirm the successful preparation of the polymer. In the spectrum of PF127-S, the characteristic peak of the C=O stretching vibration of the ester appeared at 1740 cm -1 , indicating that the end groups of the PF127 chains were successfully modified by LA.
[0122] Aniracetam is a drug that improves brain function by enhancing the activity of phospholipases in neuronal synapses and increasing the formation and transport of ATP in the brain.
[0123] The UV spectroscopy results showed that PSA NPs presented a characteristic peak at 220 nm, indicating that aniracetam was successfully loaded into PSA NPs.
[0124] The sizes of PS NPs and PS ANPs were 190.00 ± 3.56 nm and 212.74 ± 6.68 nm, respectively, which was consistent with the morphology of the nanoparticles before and after drug loading observed by transmission electron microscopy. The transmission electron microscopy pattern showed spherical shape with uniform size, and the nanoparticles had no obvious aggregation and precipitation.
[0125] The surface charge of the nanoparticles was further tested. Due to the positive charge of aniracetam, the zeta potential value of PS NPs was lower than that of PSA NPs. This change confirmed the successful preparation of PSANPs; the ultraviolet absorption of aniracetam appeared at 220 nm in PSA NPs, but not in PSNPs, which was consistent with the results of UV spectroscopy.
[0126] The in vitro antioxidant properties of PSA NPs were evaluated by DPPH scavenging experiments to verify their ability to act as an antioxidant buffer. As the concentration of PSANPs increased, the scavenging rate of DPPH gradually increased ( Figure 3 ), which indicates that PSA NPs have an effective active oxygen scavenging effect. When the concentration of PSA NPs was 6 mg / mL, the DPPH scavenging rate was 46.70± 6.42%, which was not statistically significant compared with 8 mg / mL and 10 mg / mL. Therefore, PSA NPs with a concentration of 6 mg / mL were used to prepare HA / GM / PSA hydrogels in subsequent experiments.
[0127] SEM images showed that HA / GM, HA / GM / PS, and HA / GM / PSA hydrogels were loose and porous with relatively uniform pore sizes, indicating that the addition of PS NPs and PSA NPs had no destructive effect on the structure of the hydrogels. PS NPs and PSA NPs also appeared in HA / GM / PS and HA / GM / PSA hydrogels, respectively, indicating that the nanoparticles were successfully adsorbed and the overall structure remained unchanged.
[0128] The electrical properties of HA / GM / PSA hydrogel were further confirmed by electrochemical workstation analysis. Figure 4 AC). The electronic properties of HA and HA / GM / PSA hydrogels were evaluated by cyclic voltammetry (CV). The CV scanning curve of HA / GM / PSA hydrogel showed a pair of redox peaks at -0.30 V and 0.23 V ( Figure 4 A). Compared with the current response of HA hydrogel, the oxidation and reduction currents of HA / GM / PSA hydrogel were stronger, indicating that it has higher redox activity ( Figure 4 A). The HA / GM / PSA hydrogel was subjected to 4 CV cycles in the potential range of -1.0-1.0 V to study its electrochemical stability. After 4 charge-discharge cycles, the CV curves almost completely overlapped, indicating that the HA / GM / PSA hydrogel has excellent electrochemical stability. Bode plot ( Figure 4 B) shows that the impedance of HA / GM / PSA hydrogel (465Ω) is significantly lower than that of HA hydrogel (630Ω). This result indicates that charge transfer is more likely to occur in HA / GM / PSA hydrogel.
[0129] The Nyquist curve also shows that the impedance of HA / GM / PSA hydrogel is significantly lower than that of HA hydrogel ( Figure 4 C). The charge transfer resistance of HA / GM / PSA hydrogel is lower than that of HA hydrogel, resulting in a smaller interfacial resistance between the hydrogel and tissue. These results confirm that HA / GM / PSA hydrogel has high conductivity and electrochemical stability.
[0130] Two PBS buffers (pH = 7.4; PBS pH = 6.5, containing 200 μM H 2 O 2 ) were used to simulate the physiological and pathological microenvironments in vivo, and to conduct in vitro drug release experiments on HA / GM / PSA hydrogels. Figure 4 D It can be seen that there is no sudden release of aniracetam in both cases, indicating that the HA / GM / PSA hydrogel of the present invention can effectively control the sustained and slow release of aniracetam. 2 O 2 ) was always higher than that in another PBS (pH=7.4). This is due to the rupture of the boronic acid bonds of the hydrogel and the cleavage of the disulfide bonds of LA, resulting in the accelerated release of aniracetam.
[0131] The above experimental results show that the HA / GM / PSA hydrogel of the present invention has good antioxidant effect, high conductivity and electrochemical stability, has a modulus matching that of the mouse cerebral cortex, and can effectively control the sustained and slow release of aniracetam, and is suitable for injection and filling in the cerebral infarction area for IS treatment.
[0132] Experimental Example 3. Evaluation of multifunctional hydrogel on the reversal of neurological function in mice after IS surgery
[0133] 1. Experimental methods
[0134] Behavioral Assessment:
[0135] All behavioral tests were recorded and analyzed by an experimenter blinded to group assignment.
[0136] The rotarod test was used to assess the motor activity of mice. The photochemical thrombosis (PT) animal model is a known experimental model for simulating ischemic stroke. Before inducing the PT animal model, mice were trained for 5 days. During the training period, each mouse was placed on a rotating drum that accelerated at 3 to 10 rpm for 300 seconds. The time it took for each mouse to fall off the drum was recorded as a latency measurement. The open field test was used to assess the willingness to explore the environment and the general motor activity level. Briefly, mice were gently removed from their cages and immediately placed in the center of the arena (30 cm × 30 cm, 34 cm high). The mice were allowed to explore the new environment for 5 minutes, and a total of 5 minutes were recorded, and the average walking speed and total distance were analyzed offline.
[0137] The photochemically induced PT model method is to use photosensitive substances to generate free radicals under monochrome green, directly damaging vascular endothelial cells, causing them to produce lipid peroxides, promoting platelet aggregation, activating the coagulation process, forming thrombi, blocking blood vessels and causing ischemia.
[0138] To study the effect of HA / GM / PSA hydrogel on nerve function, the model mice were randomly divided into 4 groups, one of which was the model group (PT group) and the other 3 were the treatment groups, namely HA / GM hydrogel group, HA / GM / PS hydrogel group, and HA / GM / PS hydrogel group. The sham operation group (Sham group) was used as the control. There were 10 mice in each group. The treatment groups were injected with 4 μL of the corresponding hydrogel in situ for treatment. After 4 weeks of treatment, the open field test was used to evaluate the recovery of the motor function of the mice.
[0139] 2. Experimental results
[0140] Rotarod test data ( Figure 5 A) shows that the sham-operated group can almost avoid falling in the 300-s experiment. The falling time of the mice in the HA / GM / PSA hydrogel group was about 300 s after 4 weeks, which means that the recovery of motor function of the mice in the HA / GM / PSA group was better than that in the other groups, proving that the conductive hydrogel combined with drug treatment has a significant effect on nerve repair.
[0141] The open field test was used to evaluate the recovery of the mice's motor function. The distance distribution after 4 weeks was more uniform than that after 1 week, indicating that the motor function of these mice had recovered to a certain extent. In addition, the total distance ( Figure 5 B) and movement speed ( Figure 5C) reflects the motor ability of mice. The total walking distance of mice in the HA / GM group and the HA / GM / PS hydrogel group was significantly lower than that in the HA / GM / PSA hydrogel group. The results showed that the motor ability of mice in the HA / GM / PSA hydrogel group recovered better. The results showed that after 4 weeks, there was no significant difference in the movement speed between the mice in the HA / GM / PSA hydrogel group and the mice in the sham operation group.
[0142] The above behavioral test results showed that the neurological and motor functions of mice in the HA / GM / PSA hydrogel group recovered best.
[0143] In summary, the present invention provides an electroactive multifunctional hydrogel and its preparation method and use. In the present invention, gelatin-polyaniline-3-aminobenzenesulfonic acid-3-aminophenylboronic acid polymer (GM) and methacrylated hyaluronic acid (HAMA) are subjected to free radical polymerization, and a double-crosslinked electroactive hydrogel is obtained through non-covalent crosslinking of GM dynamic boronate bonds and negatively charged HAMA; nanoparticles (PSA NPs) loaded with the drug aniracetam are further introduced into the double-crosslinked electroactive hydrogel to prepare an electroactive multifunctional hydrogel similar to ECM. The electroactive multifunctional hydrogel of the present invention can provide continuous conductivity, exert antioxidant effects in turn, inhibit inflammation and apoptosis, continuously release the drug aniracetam, and be used for later nerve repair, effectively solving the challenge of interruption of bioelectric signals in the infarct area, and proposing a promising new method for sequential treatment of ischemic stroke.
Claims
1. An electroactive multifunctional hydrogel, characterized in that: The raw materials of the electroactive multifunctional hydrogel include conductive polymer and methacrylated hyaluronic acid, wherein the conductive polymer is a product obtained by reacting gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid as raw materials under the action of an initiator; the preparation method of the electroactive multifunctional hydrogel includes the following steps: reacting the conductive polymer and methacrylated hyaluronic acid in an aqueous solution under the action of a peroxide and an amine compound to obtain the hydrogel.
2. The electroactive multifunctional hydrogel according to claim 1, characterized in that: The mass ratio of the conductive polymer to the methacrylated hyaluronic acid is 0.5-3:8; The ratio of the gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid is 15-25 g: 600-650 μL: 1.5-2.5 g: 4.0-6.0 g, the initiator is a peroxide initiator, and the mass ratio of the gelatin to the initiator is 3-5:
1.
3. The electroactive multifunctional hydrogel according to claim 2, characterized in that: The mass ratio of the conductive polymer to the methacrylated hyaluronic acid is 2:8; The ratio of the gelatin, aniline, 3-aminophenylboronic acid and 3-aminobenzenesulfonic acid is 20g:630μL:1.8g:5.0g, the peroxide initiator is ammonium persulfate, and the mass ratio of the gelatin to the initiator is 4:
1.
4. The electroactive multifunctional hydrogel according to any one of claims 1 to 3, characterized in that: The raw materials of the electroactive multifunctional hydrogel also include nanoparticles, and the preparation method of the nanoparticles includes the following steps: a non-ionic surfactant and an antioxidant compound react to obtain an intermediate product, the intermediate product is dissolved in an organic solvent, concentrated, dispersed in an aqueous solution, and dried to obtain the hydrogel; the organic solvent is an organic solvent containing a brain function improving drug, the non-ionic surfactant is Pluronic F127, the antioxidant compound is lipoic acid, and the brain function improving drug is aniracetam; the preparation method of the electroactive multifunctional hydrogel includes the following steps: a conductive polymer and methacrylated hyaluronic acid react in an aqueous solution under the action of a peroxide and a diamine compound, the obtained product is dried, and then immersed in an aqueous solution of nanoparticles and taken out to obtain the hydrogel.
5. The electroactive multifunctional hydrogel according to claim 4, characterized in that The mass ratio of the nonionic surfactant to the antioxidant compound is (13-17):1, and the mass ratio of the intermediate product to the brain function improving drug is (1.5-2.0):
1.
6. A method for preparing the electroactive multifunctional hydrogel according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: reacting a conductive polymer and methacrylated hyaluronic acid in an aqueous solution under the action of a peroxide and an amine compound to obtain; Alternatively, the method comprises the following steps: reacting the conductive polymer and methacrylated hyaluronic acid in an aqueous solution under the action of peroxide and diamine compounds, drying the obtained product, then immersing it in an aqueous solution of nanoparticles, and taking it out to obtain the product.
7. The method according to claim 6, characterized in that The peroxide is ammonium persulfate, and the diamine compound is N,N,N',N'-tetramethylethylenediamine; in the aqueous solution of the nanoparticles, the concentration of the nanoparticles is 6-10 mg / mL.
8. Use of the electroactive multifunctional hydrogel according to any one of claims 1 to 5 in the preparation of a medicament for treating and / or preventing ischemic stroke.
9. The use according to claim 8, characterized in that The drug is an in-situ gel for injection.